Spontaneous Heterotopic Triplet Pregnancy with a Two Viable Intrauterine Embryos and an Ectopic One with Right Tubal Rupture - Guimarães, Adriano Carvalho; Reis, Luciano Dias de Oliveira; Leite, Fabio Chaves; Reis, Cassiana Franco Dias dos; Costa, Alex Paula; Araujo, Walter Junior Boim de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Heterotopic pregnancy (HP) is defined as the simultaneous development of an intra- and an extra uterine gestation. The occurrence of a spontaneous triplet HP is an exceptionally rare medical condition. We report the case of a young woman with spontaneous heterotopic triplets at 8 weeks of gestation, with a misdiagnosis of topic twins and acute appendicitis. The ectopic tubal pregnancy was ruptured and a salpingectomy was performed by laparotomy. The intrauterine pregnancy progressed uneventfully. The two healthy babies were delivery by cesarean section at 36 ± 2 weeks of gestation. Heterotopic triplets with ruptured tubal ectopic pregnancy represent a special diagnostic and therapeutic challenge for the obstetrician. A high rate of clinical suspicion and timely treatment by laparotomy or laparoscopy can preserve the intrauterine gestation with a successful outcome of the pregnancy.
Keywords: obstetrical surgery; pregnancy complications; heterotopic pregnancy; multiple pregnancy; tubal pregnancy